A Meta-Analytic Structural Equation Modeling among Knowledge, Attitudes and Behaviors toward Sufficiency Economy Philosophy in Thailand - Tongsamsi, Isara; Tongsamsi, Kanyaprin (Ph.D. in Social Sciences Journal, 2024)
This research article aims to study a meta-analysis utilizing a structural equation model of knowledge, attitude, and behaviors in Thailand in line with the sufficiency economy philosophy. The “population” quantitative research study examines the correlation between variables from 2012 to 2021, with a total of 36 subjects utilizing PRISMA 2020 for both inclusion and exclusion. Three experts check the content validity of the research tools, which include a research quality assessment form and a summary of research features. Every question exhibited an index of item objective congruence (IOC) surpassing .50. The research project passed screening by the Human Research Ethics Committee. Using a one-step structural equation model with path analysis and moderator variable analysis, all data were meta-analyzed. Researchers analyzed the data using the computer program webMASEM. Findings are as follows: knowledge has a direct influence on attitude (β = .157, p = .030), but knowledge has no direct influence on behavior in living according to the philosophy of sufficiency economy (β = .094, p = .070). Attitude has a direct influence on the behavior of living according to the philosophy of sufficiency economy (β = .381, p <.001), and knowledge has an indirect influence on the behavior through sufficiency economy attitude statistically significant at the .05 level (β = .060, p = .042). The moderator test found that the sample size has moderating on the influence coefficient between knowledge and sufficiency economy attitude.